In vivo evaluation of anticryptosporidiosis activity of the methanolic extract of the plant Umbilicus rupestris (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Benhouda A, Benhouda D, Yahia M. 2019. In vivo evaluation of anticryptosporidiosis activity of the methanolic extract of the plant Umbilicus rupestris. Biodiversitas 20: 3478-3483. Umbilicus rupestris (Crassulaceae) is a medicinal plant used in general traditional medicine to cure inflammation and irritation of the skin. The present research is aimed to evaluate the antiparasitic activity of the methanolic extract of the plant URMeOH of U. rupestris against the Cryptosporidium infection in immunocompetent and immunosuppressed rats experimentally infected. Twenty-one female rats were divided into two groups. Control group (group I) and experimental group (Group II). The group I was further divided into three equal groups (normal group infected and immunosuppressed infected group). The experimental group was divided into two immunosuppressed and four equal groups and two immunocompetent infected. Cryptosporidium oocysts were isolated from bovine species stools and used to infect rats. Experimental subgroups received URMeOH two as dose 100mg/kg b.w. and 200 mg/kg b.w. and continued until 15 days. Two weeks after the administration of URMeOH, feces of rats were examined for the detection of Cryptosporidium oocysts by Ziehl-Neelsen and immunofluorescence techniques, the animals were sacrificed; their small intestines were processed and examined for the detection of pathological lesions after histopathological study. In addition, the activity of myeloperoxidase (MPO) was measured in sections of the jejunum. Concerned the results, we observed a statistically significant (P
Keywords: Algeria, Cryptosporidium, Umbilicus rupestris, immunofluorescence, MPO, oocysts